PERSEPSI KONSUMEN TERHADAP PRODUK MAHASISWA BERKEBUTUHAN KHUSUS DI POLITEKNIK NEGERI JAKARTA - Genesa Vernanda; Rahma Nur Praptiwi; Tika Dwi Ariyanti; Innas Rovino Katuruni; Maria Nino Istia (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
This study aims to identify and analyze consumer perceptions of entrepreneurial products produced by students with special needs at the Jakarta State Polytechnic (PNJ). Vocational education plays a crucial role in promoting student independence, including those with disabilities, through inclusive entrepreneurship programs. Students with special needs are capable of producing creative and marketable products but still face challenges in promotion, public perception, and market access. This research applied a survey method using online questionnaires and field observations, employing a cross-sectional study design. The findings indicate that consumers generally respond positively to the products, especially regarding quality and innovation. However, there are several aspects that need improvement, such as promotional activities, packaging design, product variety, and legal compliance. These results provide valuable insights for developing inclusive entrepreneurship strategies in vocational higher education settings and support the economic empowerment of vulnerable groups.